2021
DOI: 10.3390/s21051619
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of a Novel Interferometric Microwave Radiometer for Human Body Temperature Measurement

Abstract: In this paper, the key technology of interferometric microwave thermometer is studied, the research can be applied to the temperature measurement of human body and subcutaneous tissue. This paper proposes a hardware architecture of interferometric microwave thermometer with 2 GHz bandwidth, in which the phase shifter is used to correct phase error and the quadrature demodulator is used to realize autocorrelation detection function. The results show that when input power is 7 dBm, the detection sensitivity can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…In Figure 10b, the comparison of MSE values during the convergence of the other three algorithms except for the PSO algorithm shows that by combining the advantages of PSO and LM algorithms, the PSO-LM-BP algorithm improves the iteration efficiency and accuracy, makes it difficult for the network to converge to the local minimum, and reduces the fluctuation of temperature prediction of the broadband correlative microwave radiometer compared with the traditional BP neural network. The inversion algorithm of the correlative microwave temperature measuring system in this paper is compared with the paper on temperature measurement by a microwave radiometer published by Sun et al [24]; the results are shown in Table 5. The inversion algorithm of the correlative microwave temperature measuring system in this paper is compared with the paper on temperature measurement by a microwave radiometer published by Sun et al [24]; the results are shown in Table 5.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In Figure 10b, the comparison of MSE values during the convergence of the other three algorithms except for the PSO algorithm shows that by combining the advantages of PSO and LM algorithms, the PSO-LM-BP algorithm improves the iteration efficiency and accuracy, makes it difficult for the network to converge to the local minimum, and reduces the fluctuation of temperature prediction of the broadband correlative microwave radiometer compared with the traditional BP neural network. The inversion algorithm of the correlative microwave temperature measuring system in this paper is compared with the paper on temperature measurement by a microwave radiometer published by Sun et al [24]; the results are shown in Table 5. The inversion algorithm of the correlative microwave temperature measuring system in this paper is compared with the paper on temperature measurement by a microwave radiometer published by Sun et al [24]; the results are shown in Table 5.…”
Section: Resultsmentioning
confidence: 99%
“…The inversion algorithm of the correlative microwave temperature measuring system in this paper is compared with the paper on temperature measurement by a microwave radiometer published by Sun et al [24]; the results are shown in Table 5. The inversion algorithm of the correlative microwave temperature measuring system in this paper is compared with the paper on temperature measurement by a microwave radiometer published by Sun et al [24]; the results are shown in Table 5. The PSO algorithm is used to determine the initial network weight parameters due to its global search property, and then, the second derivative information of the LM algorithm is combined to accelerate the convergence speed and improve the iteration efficiency; finally, an innovative PSO-LM-BP high-precision inversion algorithm is proposed in this paper.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Handayani, in her research in 2019, made a thermometer calibration media using the DS1820 sensor as the temperature sensor and a dry heater as the heating medium with a humidity sensor. The drawback of this study is that the media used still has an error value between the display of the device and the thermometer compared [10]. Ardelina in 2019 also calibrated a thermometer using the LM35 sensor as the temperature sensor and a dry heater as the heating medium.…”
Section: Introductionmentioning
confidence: 99%